2006
DOI: 10.1007/s00125-006-0351-z
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and incident type 2 diabetes: risk or protection?

Abstract: Aims/hypothesis The aim of this study was to investigate the association of leptin levels with incident diabetes in middle-aged adults, taking into account factors purportedly related to leptin resistance. Subjects and methods We conducted a case-cohort study (570 incident diabetes cases and 530 non-cases) representing the 9-year experience of 10,275 participants of the Atherosclerosis Risk in Communities Study. Plasma leptin was measured by direct sandwich ELISA. Results In proportional hazards models adjusti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
111
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 47 publications
9
111
0
3
Order By: Relevance
“…Instead, they reported that obesity and insulin resistance explained most of the association between leptin and subsequent diabetes risk. Other studies also suggest that abdominal adiposity may modulate the association between leptin and type 2 diabetes [9,12,14,15,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they reported that obesity and insulin resistance explained most of the association between leptin and subsequent diabetes risk. Other studies also suggest that abdominal adiposity may modulate the association between leptin and type 2 diabetes [9,12,14,15,25].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between adipokines and the onset of type 2 diabetes in middle-aged men: The PRIME study. Diabetes Research and Clinical Practice, 120,[24][25][26][27][28][29][30] Publisher rights © 2016 Elsevier Ltd. This manuscript version is made available under the CC-BY-NC-ND 4.0 license http://creativecommons.org/licenses/bync-nd/4.0/which permits distribution and reproduction for non-commercial purposes, provided the author and source are cited.…”
mentioning
confidence: 99%
“…In contrast, the ARIC study was based on a total of 581 cases (229 men and 352 women) [2]. Small sample size also increases the risk of multicollinearity.…”
mentioning
confidence: 99%
“…To the Editor: We thank Snijder et al for sharing their data from the Hoorn Study [1] and for their interpretation of the protective associations we reported between leptin and incident diabetes in middle-aged adults from the Atherosclerosis Risk in Communities (ARIC) study [2].…”
mentioning
confidence: 99%
See 1 more Smart Citation